Challenges in Identifying High-Leverage Practices. Issue 7 (July 2015) - Cohen, Julie
Background: The current accountability climate prioritizes identifying features of "effective teaching." One approach has to been to outline a set of "high-leverage practices, " defined as teaching moves that are research-based, have the potential to improve student achievement, and support students in learning central academic concepts. But which practices qualify as "high leverage, " and based on what criteria? This article raises several issues involved in identifying "high-leverage" teaching practices based on their relationships with different types of student outcome measures. Purpose: The study addresses the following research questions: What practices are associated with student achievement gains on high- and low-stakes assessments? How do teachers use these teaching practices in their classrooms? Population: Participants in this study were 103 fourth grade teachers from a single district who volunteered to have their classroom instruction recorded as part of the Bill and Melinda Gates Foundation's Measures of Effective Teaching (MET) project. Research Design: The research involved analysis of multiple data sources: video records of practice, qualitative observation notes, quantitative measures of math teaching, and student outcomes on two math assessments, one high stakes comprised entirely of multiple-choice questions and the other low stakes and focused on open-ended problem solving. Data Analysis: A standardized observation tool designed to code language arts instruction, PLATO, was modified for reliable scoring of math teaching. More than 300 math lessons were scored using four PLATO scales. Logistic regressions were used to look at relationships between PLATO scores and teacher value-added measures computed from high- and low-stakes student assessments. A stratified, purposive sample of lessons was analyzed qualitatively. Findings/Results: Scores on two practices, modeling and procedural strategy instruction, predicted value-added based on the high-stakes state test, but had no relationship with value-added on the low-stakes test. Qualitative analyses demonstrate instruction was explicitly oriented toward success on the state test. Teachers taught test-taking strategies and modeled how to eliminate "silly" answers listed in multiple-choice format. Two other practices, orchestrating classroom discourse and conceptual strategy instruction, had no relationship with value-added on either test. Scores on these two scales were positively skewed, with very few instances of high-scoring instruction. Conclusions/Recommendations: Discussion focuses on potential limitations of labeling teaching practices as "high leverage" based on their relationship with high-stakes standardized assessments and the importance of sampling teachers with a full range of enactment of high-leverage practices.